2020
DOI: 10.3389/fpls.2020.573126
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying the Effects of Vegetation Restorations on the Soil Erosion Export and Nutrient Loss on the Loess Plateau

Abstract: The transport of eroded soil to rivers changes the nutrient cycles of river ecosystems and has significant impacts on the regional eco-environment and human health. The Loess Plateau, a leading vegetation restoration region in China and the world, has experienced severe soil erosion and nutrient loss, however, the extent to which vegetation restoration prevents soil erosion export (to rivers) and it caused nutrient loss is unknown. To evaluate the effects of the first stage of the Grain for Green Project (GFGP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 80 publications
1
11
0
Order By: Relevance
“…From the spatial regression model, we found that the value of ecosystem services is affected by its grid cell elements but also by neighboring grid cells or more distant grid cell elements. This means that the concentration of population and economy does not automatically lead to the degradation of ecological services [ 40 , 41 , 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…From the spatial regression model, we found that the value of ecosystem services is affected by its grid cell elements but also by neighboring grid cells or more distant grid cell elements. This means that the concentration of population and economy does not automatically lead to the degradation of ecological services [ 40 , 41 , 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…In particular, the rapid economic development in Northwest China has led to substantial imbalances between the natural environment and industrial development. The Loess Plateau, mainly located in the middle reach of the Yellow River, is considered as one of the regions with the most severely eroded areas in the world, and the soil loss has significantly impacted nutrient losses (Zhao et al 2020a). Further, the Yellow River is facing the problem of water quality deterioration with the rapid development of the social economy.…”
Section: Introductionmentioning
confidence: 99%
“…To effectively control soil erosion and ecological degradation, the Chinese government implemented the “Grain for Green Project” (GGP) since 1999 to return farmland with slopes of 25° or more to perennial vegetation [ 2 , 17 , 18 ]. Vegetation restoration triggered by the “GGP” is an effective approach to ecological construction and soil erosion control in the western region of China [ 19 , 20 , 21 ]. Since the implementation of the “GGP”, the soil erosion environment in the Loess Plateau has been greatly changed by large-scale vegetation restoration [ 2 , 9 , 17 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Vegetation restoration triggered by the “GGP” is an effective approach to ecological construction and soil erosion control in the western region of China [ 19 , 20 , 21 ]. Since the implementation of the “GGP”, the soil erosion environment in the Loess Plateau has been greatly changed by large-scale vegetation restoration [ 2 , 9 , 17 , 18 , 19 ]. The United Nations General Assembly announced the “United Nations Decade on Ecosystem Restoration 2021–2030 (UNDER)” on 1 March 2019, a movement aimed to expand the restoration of degraded and damaged ecosystems as an effective measure to address the climate crisis and enhance food security, water resources, and biodiversity [ 1 , 22 ].…”
Section: Introductionmentioning
confidence: 99%